Adhesion Molecules Involved in Stem Cell Niche Retention During Normal Haematopoiesis and in Acute Myeloid Leukaemia - Grenier, Julien M. P.; Testut, Céline; Fauriat, Cyril; Mancini, Stéphane J. C.; Aurrand-Lions, Michel (Frontiers in Immunology, 2021)
In the bone marrow (BM) of adult mammals, haematopoietic stem cells (HSCs) are retained in micro-anatomical structures by adhesion molecules that regulate HSC quiescence, proliferation and commitment. During decades, researchers have used engraftment to study the function of adhesion molecules in HSC’s homeostasis regulation. Since the 90’s, progress in genetically engineered mouse models has allowed a better understanding of adhesion molecules involved in HSCs regulation by BM niches and raised questions about the role of adhesion mechanisms in conferring drug resistance to cancer cells nested in the BM. This has been especially studied in acute myeloid leukaemia (AML) which was the first disease in which the concept of cancer stem cell (CSC) or leukemic stem cells (LSCs) was demonstrated. In AML, it has been proposed that LSCs propagate the disease and are able to replenish the leukemic bulk after complete remission suggesting that LSC may be endowed with drug resistance properties. However, whether such properties are due to extrinsic or intrinsic molecular mechanisms, fully or partially supported by molecular crosstalk between LSCs and surrounding BM micro-environment is still matter of debate. In this review, we focus on adhesion molecules that have been involved in HSCs or LSCs anchoring to BM niches and discuss if inhibition of such mechanism may represent new therapeutic avenues to eradicate LSCs.